Strategic planning for saving the lives of mothers, newborns and children and preventing stillbirths in KwaZulu-Natal province South Africa: modelling using the Lives Saved Tool (LiST). (December 2015) - McGee, Shelley-Ann; Chola, Lumbwe; Tugendhaft, Aviva; Mubaiwa, Victoria; Moran, Neil; McKerrow, Neil; Kamugisha, Leonard; Hofman, Karen
Abstract Background KwaZulu-Natal province in South Africa has the largest population of children under the age of five and experiences the highest number of child births per annum in the country. Its population has also been ravaged by the dual epidemics of HIV and TB and it has struggled to meet targets for maternal and child mortality. In South Africa's federal system, provinces have decision-making power on the prioritization and allocation of resources within their jurisdiction. As part of strategic planning for 2015–2019, KwaZulu-Natal provincial authorities requested an assessment of current mortality levels in the province and identification and costing of priority interventions for saving additional maternal, newborn and child lives, as well as preventing stillbirths in the province. Methods The Lives Saved Tool (LiST) was used to determine the set of interventions, which could save the most additional maternal and child lives and prevent stillbirths from 2015–2019, and the costs of these. The impact of family planning was assessed using two scenarios by increasing baseline coverage of modern contraception by 0.5 percentage points or 1 percentage point per annum. Results A total of 7, 043 additional child and 297 additional maternal lives could be saved, and 2, 000 stillbirths could be prevented over five years. Seventeen interventions account for 75 % of additional lives saved. Increasing family planning contributes to a further reduction of up to 137 maternal and 3, 168 child deaths. The set of priority interventions scaled up to achievable levels, with no increase in contraception would require an additional US91 million over five years or US1.72 per capita population per year. By increasing contraceptive prevalence by one percentage point per year, overall costs to scale up to achievable coverage package, decrease by US24 million over five years. Conclusion Focused attention on a set of key interventions could have a significant impact on averting stillbirths and maternal and neonatal mortality in KwaZulu-Natal. Concerted effort to prioritize family planning will save more lives overall and has the potential to decrease costs in other areas of maternal and child care.